Phosphorus-Doped Perovskite Oxide as Highly Efficient Water Oxidation Electrocatalyst in Alkaline Solution - Zhu, Y.; Zhou, W.; Sunarso, J.; Zhong, Y.; Shao, Zongping (Wiley, 2016)
Developing cost-effective and efficient electrocatalysts for oxygen evolution reaction (OER) is of paramount importance for the storage of renewable energies. Perovskite oxides serve as attractive candidates given their structural and compositional flexibility in addition to high intrinsic catalytic activity. In a departure from the conventional doping approach utilizing metal elements only, here it is shown that non-metal element doping provides an another attractive avenue to optimize the structure stability and OER performance of perovskite oxides. This is exemplified by a novel tetragonal perovskite developed in this work, i.e., SrCo0.95P0.05O3– δ (SCP) which features higher electrical conductivity and larger amount of O2 2−/O− species relative to the non-doped parent SrCoO3– δ (SC), and thus shows improved OER activity. Also, the performance of SCP compares favorably to that of well-developed perovskite oxides reported. More importantly, an unusual activation process with enhanced activity during accelerated durability test (ADT) is observed for SCP, whereas SC delivers deactivation for the OER. Such an activation phenomenon for SCP may be primarily attributed to the in situ formation of active A-site-deficient structure on the surface and the increased electrochemical surface area during ADT. The concept presented here bolsters the prospect to develop a viable alternative to precious metal-based catalysts.